LEGAL STUDIES OF LAW NUMBER 13 OF 2003 CONCERNING LABOR IN TERMS OF MINIMUM WAGE - Anita (DE RECHT (Journal of Police and Law Enforcement), 2024)
The judge's decision must be considered correct until there is a higher decision that annuls it. The judge's decision must be based on the principles of real justice not mere procedural justice. the judge's decision must be based on the applicable laws and regulations. Sentencing, legal remedies and execution of criminal decisions have been stipulated in the Criminal Code (KUHP). In the implementation of execution against the defendant, supervision is carried out by the judge. This is to ensure that the implementation is in accordance with the verdict and is carried out properly.